Case report: Asp194Ala variant in MFN2 is associated with ALS-FTD in an Italian family - Vinciguerra, C.; Di Fonzo, A.; Monfrini, E.; Ronchi, D.; Cuoco, S.; Piscosquito, G.; Barone, P.; Pellecchia, M. T (Frontiers in Genetics, 2023)
Abstract Word count: 233 Background: MFN2 gene encodes the protein Mitofusin 2, involved in essential mitochondrial functions such as fusion, trafficking, turnover, and cellular interactions. We describe a family carrying a novel MFN2 mutation associated with ALS-frontotemporal dementia (FTD) clinical phenotype in the mother and Charcot-Marie-Tooth disease type 2A (CMT2A) in her son. Case presentation: The mother, a 67-year-old woman, referred to us for a three year-history of mood disturbance and gait impairment, and a more recent hypophonia, dysarthria, dysphagia, and diffuse muscle wasting. Family history was positive for psychiatric disorders and gait disturbances. Brain 18F-FDG PET showed severe hypometabolism in the fronto-temporal brain cortex bilaterally. Electrodiagnostic studies (EDX) showed severe motor axonopathy in the bulbar, cervical and lumbosacral districts. Her 41-year-old son had a history of mood depression and sensory disturbances in the limbs, along with mild muscle wasting, weakness, and reduced reflexes. Nerve conduction studies revealed a moderate sensory-motor polyneuropathy, while brain MRI was normal. Whole exome sequencing of the patients’ DNA identified the novel MFN2 (NM_014874.4) variant c.581A>C p.(Asp194Ala). Conclusions: Our findings provide evidence of heterogenous clinical manifestations in family members sharing the same MFN2 molecular defect. Additionally, we present the first documented case of ASL-FTD associated with an MFN2 mutation, thereby expanding the range of MFN-related disorders. Further research involving larger cohorts of patients will be needed to better understand the role of MFN2 as a contributing gene in the development of ALS-FTD.